Culture and religion as sources of gender inequality: rethinking challenges women face in contemporary Africa - Rwafa, Urther (Taylor & Francis (Routledge), 2016)
The aim of this article is to explore how the contentious issues of culture and religion remain sources of gender inequality and oppression for most women in Africa. Culture refers to the “learned and ideational aspects of human society” (Jenks 1993: 9). In its subjectivity, culture carries the illusion of shared concerns and values in the face of the real and contentious divisions that exist among classes, gender, race and ethnic groups. Religion refers to what people believe in; their spirituality and how this shapes people's relation with each other and with God – the Almighty. In this article, the concept of “gender” shall be taken to mean roles that are ascribed to men and women. More often than not, these roles can be presented as if they are “fixed”, “unchangeable” and “incontestable”. Culture, religion and gender are problematic terminologies that merit analysis within the context of how these are used in some African communities to justify the oppression of women. In this endeavour, the article will pay special attention to how factors such as biblical notions of the creation of man, polygamy, cultural beliefs on spirit mediums, education, violence, forced marriages, women and property ownership, as well as cultural practices such as circumcision have informed cultural and religious decisions to justify the oppression of women in contemporary Africa. The central argument of this article is that since culture and religion are socially constructed, the manner in which they define gender roles in Africa can be challenged. The idea is to interrogate, deconstruct and demystify gender stereotypes that are constructed by culture and religion to discourage women from participating fully in the development of contemporary Africa.